Investigation of fluid dynamic parameters in packed distillation columns using X-ray computed tomography - Schug, Sebastian; Kohler, Tobias; Arlt, Wolfgang (Separations Division 2014 - Core Programming Area at the 2014 AIChE Annual Meeting, 2014)

Potential analysis for the improvement of chemical energy transformation processes - Adametz, Patrick; Baumgärtner, Andrea; Kohler, Tobias; Obermeier, Jonas; Siebert, Daniel; Müller, Karsten (Chemical Engineering & Technology, 2017)
Much research aims to improve the efficiency of energy processes. However, it is often not clear where the biggest potential for improvement lies. Crucial for a namable improvement is a realistic chance for advancing the respective element as well as a significant influence of the respective element on the overall performance. A study on the potential for improving the efficiency of five exemplary chemical-energy systems is presented. It was found that replacing working substances by alternatives with better enthalpies of reactions or solubility behavior carries huge potential for improving energy processes. However, in most cases there is little potential, for example, in lower heat capacity, even though heat capacity highly influences the efficiency of the processes.

Temperature independent description of water adsorption on zeotypes showing a type V adsorption isotherm - Kohler, Tobias; Hinze, Moritz; Müller, Karsten; Schwieger, Wilhelm (Energy, 2017)
New adsorbents like aluminumphosphates (AIPO's) and siliconaluminumphosphates (SAPO's) show high potential for adsorption based heat transformation processes. These adsorbents show IUPAC type V adsorption behavior with the adsorptive water. To model heat transformation processes it is important to describe the adsorption equilibrium independent of temperature. Many groups in this research field use the potential theory by Polanyi to model the adsorption process. However, the classical potential theory is not suited to describe type V adsorption behavior. This work presents an adaption of the potential theory, which enables the temperature independent modeling of the adsorption of water on zeotypes showing a type V adsorption characteristic. The adaption is based on a corrected adsorption enthalpy and consequently on a more valid description of the desorption pressure. The adaption could be verified through our own experiments on ALPO-18, SAPO-18 and TAPSO-34 adsorbents, as well as with isotherms for ALPO-5 from literature, measured at different temperatures using water as adsorptive. The results show that the presented adaption is able to describe the adsorption equilibrium independent of temperature and therefore enables modeling of adsorption based heat transformation processes with the potential theory of adsorption. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Adsorption refrigeration; Energy density; Efficiency; Characteristic curve; SAPO-18; TAPSO-34; Water adsorption